A novel computer application for scrap reporting and data management in the manufacturing of components for the automotive industry - Rodrigues, H. (2022)
30th International Conference on Flexible Automation and Intelligent Manufacturing (FAIM2021) 15-18 June 2021, Athens, Greece.